Self, reality and reason in Tibetan philosophy : Tsongkhapa's quest for the Middle Way - Thupten Jinpa (Curzon critical studies in Buddhism., 2002)
The work explores the historical and intellectual context of Tsongkhapa's philosophy and addresses the critical issues related to questions of development and originality in Tsongkhapa's thought. It also deals extensively with one of Tsongkhapa's primary concerns, namely his attempts to demonstrate that the Middle Way philosophy's deconstructive analysis does not negate the reality of the everyday world. The study's central focus, however, is the question of the existence and the nature of self. This is explored both in terms of Tsongkhapa's deconstruction of the self and his reconstruction of.